Analisis cemaran mikroba pada daging ayam broiler di beberapa pasar tradisional di Kota Binjai - Surbakti, Junaidi Lapiga; Purwosiswoyo, Purwosiswoyo; Putra, Andhika; Sinaga, Kurniawan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Broiler chickens are a source of protein consumed by the wider community, have relatively affordable prices and are very common in traditional markets. The city of Binjai has a high level of demand for broiler chicken meat, so it is important to know the level of safety in consuming broiler chicken meat in terms of microbial contamination. This research aims to analyze microbial contamination in broiler chicken meat in several traditional markets in Binjai City. This research uses a descriptive method to determine the presence of bacterial contamination in broiler chicken meat. Research parameters include observation of the number of microbial colonies and analysis of Salmonella sp. microbial contamination. and E. coli. The research results showed that the number of microbial colonies in the three markets met SNI requirements and was negative in the Salmonella sp. contamination test but contamination occurred in the Escherichia coli contamination test.